HOPE: protótipo de uma rede social com o tema doação de sangue, para ajudar a aumentar os índices de doações no município de Castanhal-PA - LIMA, Suze Blenda de Paula (2022)
This Course Conclusion Work aims to develop a conceptual prototype of a system with characteristics of a social network directed to the theme "blood donation", aiming to contribute to the increase of donations in blood centers in the city of Castanhal-PA. At work, you can follow all the stages of research, development and tests carried out, being able to serve as a guide for those who seek theoretical support on the planning of a software. The construction of the idea itself was architected from the perspective of qualitative and exploitative methodologies, so that it was possible to have a dimension of the main needs of the public, and that the applications selected for the work were really essential for the system and could contribute to the objectives from the project. The results obtained through surveys, forms and magazines made it possible to identify the main needs that people have on the topic of blood donation, which were implemented in the system prototype (validated at the end of the research by the target audience of the platform, donors and non-donors). In surveys, one can see the acceptability of this work, as 83.4% of those who participated in one of the forms, reveal interest in being a user of a platform with the objectives that HOPE, showing the real need for the project.